In-Silico Approach of Mole Crab (Emerita sp.) Peptides Produced by Alcalase Hydrolysis - Romadhon, Romadhon; Sabdono, Agus; Subagyo, Subagyo; Triyanto, Agus; Riyadi, Putut Har; Amalia, Ulfah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
One type of mole crab in Indonesia is Emerita sp., which has a fatty acid content of 3.57% and crude protein content of 32.42% (100 mg). The use of mole crabs is currently limited to food sources; therefore, it is necessary to conduct research to optimize the use of mole crabs, which are a source of protein hydrolysate. The samples were used under fresh conditions and stored at −20°C before processing. This study aimed to produce protein hydrolysates from moles of crabs. This hydrolysate is produced by enzymatic hydrolysis of marine back-down raw materials using alcalase. In silico analyses have identified the potential of marine-receding protein hydrolysates. The results of in silico analysis using BIOPEP and Peptide Ranker revealed that these peptides exhibited multiple bioactivities, including ACE inhibition, DPP-IV inhibition, and antioxidative and anti-inflammatory effects. The dipeptide PW (Pro-Trp) achieved the highest Peptide Ranker score of 0.993, with a predicted dual function as an antioxidant and DPP-IV inhibitor. Molecular docking confirmed strong binding affinities to target receptors, with the AF peptide displaying the best interaction against ACE (−129.70 kcal/mol) and GH peptide against DPP-IV (−113.68 kcal/mol). These results suggest that mole crab hydrolysate contains promising peptides with potential applications as nutraceuticals, particularly in the management of hypertension and type 2 diabetes mellitus. The highest potency based on the in-silico peptide hydrolysate has a strong antihypertensive effect. Further in vivo research is needed to explain the potential of sea retreat peptides as bioactive antihypertensive agents in peptide form.